Research, policy engagement and practice - Jones, N; Tefera, B; Woldehanna, T (2005)
This paper examines efforts to bridge multi-disciplinary research, policy engagement and practice to improve the lives of children living in poverty in a sample of developing countries. The paper is based on the experiences of Young Lives and draws on insights from Ethiopia, India, Peru, and Vietnam. It pays particular attention to the work of the Young Lives team in Ethiopia to make children’s issues central to the Ethiopian Poverty Reduction Strategy Paper process. The paper first discusses the importance of examining and understanding the policy environment in order to increase the possibility of having a pro-child influence on policy. It then considers how Young Lives in Ethiopia has set out the key factors to ensure successful research-based advocacy. The authors stress the importance of: credible research quality, understanding of the socio-political context in which research is embedded, identifying and networking with state and civil society actors, and ensuring advocacy messages are framed in a context-appropriate way. They also present lessons learned on the timing of policy engagement; the politics of bridging research and policy; and the value of long-term partnerships between NGOs and researchers. The paper concludes by reflecting on the strengths and weaknesses of the poverty reduction strategy in Ethiopia, and outlines some general lessons for translating research into social policy change.